Simultaneous Use of MutS and RecA for Suppression of Nonspecific Amplification during PCR - Fukui, Kenji; Kuramitsu, Seiki (Journal of Nucleic Acids, 2013)
Thermus thermophilus MutS, a thermostable mismatch-recognizing protein, is utilized in PCR to suppress nonspecific amplification by preventing synthesis from mismatched primers. T. thermophilus RecA also decreases nonspecific amplification by promoting proper hybridization between the primer and template. We observed that MutS and RecA function under the same reaction conditions and that MutS and RecA do not preclude each other. Furthermore, there were some DNA sequences for which only one of the 2 proteins effectively suppressed nonspecific amplification. The simultaneous use of MutS and RecA is a more attractive error-suppressing technique than the use of either of the 2 proteins alone.